Using auxiliary data to rationalize smartphone-based pre-harvest forest mensuration - Pitkänen, Timo P; Räty, Minna; Hyvönen, Pekka; Korhonen, Kari T; Vauhkonen, Jari (Oxford Academic, 2021)
Accurate mensuration of forest stands for pre-harvest planning will pose high costs if carried out by a professional forester as an on-site evaluation. The costs could be reduced if a person with limited mensuration expertise could collect the required data using a smartphone-based system such as TRESTIMA® Forest Inventory System. Without prior information, the field sample with sufficient number of measurement points over the whole stand should be selected, so that the entire variation will be covered.We present and test a rational framework based on selecting the sampling locations according to auxiliary data. As auxiliary variables,we use various spatial data sources indicating forests’ structural or spectral variation, as well as previously predicted inventory variables. We construct two variants of sampling schemes based on the local pivotal method, weighted by the auxiliary data, and compare the results to simple random sampling (SRS) with corresponding sample sizes. According to our findings, the benefits of auxiliary data depend on the considered stand, species and timber assortment. The use of auxiliary data leads generally to improved results and up to three times higher efficiency (i.e. lower variance) as compared with SRS.We conclude that the framework of applying auxiliary data has high capabilities in rationalizing the sampling efforts with little drawbacks, consequently providing potential to improve the results with similar sample size and possibility to use of non-specialists for the pre-harvest inventory.
Keywords: forest mensuration; smartphone-based systems; pre-harvest inventory